A Molecular Beacon‐Based Signal‐Off Surface‐Enhanced Raman Scattering Strategy for Highly Sensitive, Reproducible, and Multiplexed DNA Detection. Issue 15 (29th January 2013) - Wei, Xinpan; Su, Shao; Guo, Yuanyuan; Jiang, Xiangxu; Zhong, Yiling; Su, Yuanyuan; Fan, Chunhai; Lee, Shuit‐Tong; He, Yao
<x xml:space="preserve">Abstract</x> Stem‐loop oligonucleotides tagged with organic dyes are employed as capture and reporter probes in a molecular beacon‐based signal‐off surface‐ enhanced Raman scattering (SERS) strategy. DNA strands are immobilized on a gold nanoparticle‐decorated silicon nanowire array (AuNPs@SiNWAr). DNA with a concentration down to ≈10 fM is detected under irradiation from a low‐power laser, which is better than or comparable to that detected by signal‐on SERS methods. The signal‐off strategy allows identification of single‐base mismatches and detection of multiplexed DNA. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>